ACCEPTANCE OF GRIEF AND CHANGES IN FAMILY DYNAMICS IN THE FILM “BILA ESOK IBU TIADA”: A STUDY OF HERMENETICS - Chaesar, Ari Suryawati Secio; Tarigan, Nurul Husna; Asmara, Trinata; Wulandari, Wina; Pasaribu, Gumarpi Rahis (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2025)
This study examines the acceptance of grief and changes in family dynamics shown in the film